Physical Activity and Sedentary Behavior in People With Inflammatory Joint Disease: A Cross‐Sectional Study. Issue 3 (27th January 2022) - Bell, Kirsty; Hendry, Gordon; Steultjens, Martijn
Abstract : Objective: To determine whether patients with inflammatory joint disease (IJD) meet current guidelines on physical activity, and to determine which factors influence physical activity levels and sedentary behavior (SB) in patients with IJD. Methods: This was a cross‐sectional study of 137 patients with a medical diagnosis of an IJD prior to commencing an NHS‐run inflammatory arthritis exercise program. Physical activity and SB were measured objectively using a thigh‐worn physical activity monitor for 7 consecutive days. Activity levels were subdivided into low physical activity (LPA) and moderate‐to‐vigorous physical activity (MVPA). First, activity levels were analyzed against current guidelines of 150 minutes of MVPA per week. Second, time spent in SB, LPA, and MVPA was analyzed against possible determinants. Results: In total, 29% of patients with IJD met current physical activity guidelines. Patients on average spent 10 hours per day in SB. Poor physical fitness measured by the 6‐minute walk test was the only significant predictor ( P = 0.019) of high SB (R 2 = 4.7%). Attending an exercise facility in the community ( P = 0.034) and low role limitations due to physical health ( P = 0.008) predicted high levels of LPA, following a backward multiple regression (R 2 = 8.0%). Low role limitations due to emotional problems ( P = 0.031), higher physical fitness ( P = 0.002), and healthier exercise attitudes and beliefs ( P = 0.021) predicted meeting current physical activity guidelines, following a backward conditional logistic regression, explaining between 22.2% and 31.7% of variance. Conclusion: Patients with IJD are inactive and spent much time in SB. Good general health predicts high activity levels. No disease‐specific factors were found to determine SB, LPA, or MVPA.